PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI METODE HYPERSCAN PADA SISWA SMA MUHAMMADIYAH 2 PALEMBANG - Mulyati, Mulyati (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
The hyper-scan method is one way that instructors employ to help students in class XI improve their reading comprehension. Indeed, many students struggle with reading comprehension. This is a Classroom Action Research (CAR) research comprising two cycles of 4 stages: planning, action, observation, and reflection. was used to analyze the test data. The result shows the average pre-cycle score was 63.83, the first cycle score was 73.77, and the second cycle score was 84.33. According to the percentage of students who qualify, there has traditionally been an increase. The percentage of completion in pre-cycle tests ranged from 10% to 46.6 percent in the first cycle and up to 90% in the second cycle. As a result, it can be concluded that the hyper-scan method can assist in reading comprehension skills development